Remembering rituals of remembrance: Capturing Xantolo through SenseCam - Lindley, Siân; Gámez, Eduardo H. Calvillo; Leija, Juan José Gámez (CHI 2010 workshop on HCI at the End of Life., 2010)
Xantolo is a Mexican tradition in which deceased loved ones are celebrated and honoured through their re-enactment. In this paper, we outline a proposed project in which we intend to capture first-person perspectives of Xantolo via a wearable camera, SenseCam. This should give rise to a number of outcomes. Firstly, it will involve the creation of a novel record of Xantolo by capturing a first-person perspective. Secondly, it will allow participants of the event to reflect upon its practices in a different social context, hopefully allowing insights to be gained into its various rituals. Finally, the project allows the possibility of reflecting upon a deceased relative by re-visiting their re-enactment, a process that is somewhat specific to Xantolo, but that may nevertheless inspire the design of interactive systems for more general remembrance.